The value of sacrifice in (post-)growth scenarios. Issue 1 (31st December 2022) - Cojanu, Valentin
Abstract: This is a conceptual paper, which contributes to the debate on the measure of intergenerational sacrifice and advances a post-growth theoretical framework that becomes intelligible within a wider space of deliberation, at once economic, social, and moral. We explore the three-pronged argument in two parts. First, we examine the implications of the socio-economic mechanism of the transition of the production mode from extractive to generative, which is envisaged to replace the market automatic response by allocative efficiency. A second part tackles the moral reason underlying decision-making. Drawing on the lessons of the post-growth debate, we propose and defend a working definition of the moral reason of intergenerational justice that should also underpin our rationalizing about other issues of similar importance regarding the obligations we owe to future people, such as passing on languages or containing epidemics.